Prevention and Promotion Effects of Self Help Plus: Secondary Analysis of Cluster Randomised Controlled Trial Data among South Sudanese Refugee Women in Uganda - Augustinavicius Jura, Purgato Marianna, Marx .Ronald Leku, Kenneth Carswell, 6 Daniel Lakin, Eirini Karyotaki, Corrado Barbui (BMJ open, 2023)
Evidence-based and scalable prevention and promotion focused mental health and psychosocial support interventions are needed for conflict-affected populations in humanitarian settings. This study retrospectively assessed whether participation in Self Help Plus (SH+) versus enhanced usual care (EUC) resulted in reduced incidence of probable mental disorder and increased positive mental health and well-being postintervention among South Sudanese refugee women in Uganda.